MENINGKATKAN HASIL BELAJAR PENJUMLAHAN PECAHAN PENYEBUT BERBEDA DENGAN PENDEKATAN CONTECXTUAL TEACHING AND LEARNING (CTL) DI KELAS V SD - Yasmi, Yasmi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study is a class action that aims to improve learning outcomes different from the sum of fractional denominator approach Contextual Teaching and Learning (CTL) in Class V school students Bustanul Ulum Semen Padang. The approach used is a qualitative and quantitative approach. The data source is a learning process and outcomes of the implementation of the sum of fractions with different denominators using the approach of Contextual Teaching and Learning (CTL). Kata Kunci : hasil belajar siswa, penjumlahan pecahan penyebut berbeda, pendekatan contecxtual teaching and learning (ctl)